Digitization: challenges for Croatian museums - Šalamon-Cindori, Breza; Tot, Marko; Živković, Daniela (2014)
In transition to digital age, enormous challenges are posed to all the heritage institutions, including museums. Digitization of records such institutions keep in their funds is becoming more and more one of their everyday tasks, and at the same time also a manner for presenting and making available to the public use the valuable collections stored in them. This paper presents a survey conducted in March 2012 in Croatian museums about the participation of Croatian museums in digitization procedures that is in presenting the collections of Croatian museums in a digital environment.
Projekt MZOS
ENG